Synthesis and evaluation of CuNi-MOF as a corrosion inhibitor of AISI 304 and 316 stainless steel in 1N HCl solution - Alireza Veysi; Mahmoud Roushani; Hossein Najafi (Heliyon)
A bimetallic organic framework (CuNi-MOF) was synthesized as a corrosion inhibitor using the solvothermal method. The effectiveness of the inhibitor in corrosion prevention of AISI 304 and 316 in 1N hydrochloric acid solution at room temperature was evaluated using weight loss measurements, electrochemical methods, and surface characterization techniques. The formation of CuNi-MOF protective layer on the stainless-steel surface was confirmed through Field Emission Scanning Electron Microscopes (FESEM), Energy Dispersive Spectroscopy (EDS), and X-Ray Diffraction (XRD) analysis. The result showed that the synthesized inhibitor with a concentration of 150 mg/L could improve the corrosion inhibition of studied materials by up to 87.12 % for AISI 304 and 91.9 % for AISI 316, respectively. The potentiodynamic polarization data indicated the studied inhibitor acts as an anodic type inhibitor and EIS investigations revealed a significant increase in polarization resistance with addition of 150 mg/L CuNi-MOF. The study of adsorption energy (ΔGads0) revealed the Langmuir adsorption isotherm prevails in CuNi-MOF adsorption, encompassing both chemisorption and physisorption mechanisms.